2022
DOI: 10.1029/2022ef002823
|View full text |Cite
|
Sign up to set email alerts
|

The Longest Baseline Record of Vegetation Dynamics in Antarctica Reveals Acute Sensitivity to Water Availability

Abstract: Antarctica plays a central role in regulating global climatic and oceanographic patterns and is an integral part of global climate change discussions (Rogers et al., 2020). Warming and mass loss of outlet glaciers as described in the Sixth Assessment Report of the IPCC have been mainly observed in West Antarctica, whereas warming trends in East Antarctica have been seen as localized and inconsistent (Turner et al., 2009). Parts of East Antarctica are projected to experience greater-than-global warming in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…With high plasticity indicated by the rapid physiological and morphological changes in B. argenteum , the suggestion that the extreme seasonality of Antarctica leads to high resilience is supported. Additionally, B. argenteum populations in Cape Hallett studied over time have remained stable [ 54 ], which further corroborates their inherent resilience to change. Although general warming trends have not yet been exhibited across continental Antarctica [ 85 ], the region is predicted to become increasingly exposed to thermal stress in the form of heatwaves [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…With high plasticity indicated by the rapid physiological and morphological changes in B. argenteum , the suggestion that the extreme seasonality of Antarctica leads to high resilience is supported. Additionally, B. argenteum populations in Cape Hallett studied over time have remained stable [ 54 ], which further corroborates their inherent resilience to change. Although general warming trends have not yet been exhibited across continental Antarctica [ 85 ], the region is predicted to become increasingly exposed to thermal stress in the form of heatwaves [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 76%
“…With the versatility in carbon gain seen under our pulse warming treatment, mosses in continental Antarctica are likely to increase growth rates and potentially expand in coverage or density under predicted short- or long-term warming. However, enhanced growth and expansion are dependent on how increased temperatures alter water availability and permafrost active layer depth, factors which can greatly affect moss performance [ 54 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because survey periods have to span decades rather than years or seasons to allow for significant and accurate detection of growth and the establishment of robust baselines (Convey et al, 2018;Green et al, 2011;Turner et al, 2018). It is because of these complications, that so far, only three "long-term" baseline studies exist in and around Antarctica: two of them situated in the maritime Antarctic [Signy Island (Cannone et al, 2016(Cannone et al, , 2022, and Argentine Islands (Fowbert & Smith, 1994;Parnikoza et al, 2009)], and one in continental Antarctica (Brabyn et al, 2006;Colesie et al, 2022).…”
Section: Antarctic Vegetationselected For Life At the Limitsmentioning
confidence: 99%
“…The lack of baseline knowledge on moss growth and its natural variability is still limiting our ability to evaluate change. The only study, to date, to report the long-term baseline ecology of Antarctic mosses is reporting strong seasonal phenology, distribution patterns that are driven by water availability, and steady perennial growth of moss at Cape Hallett in continental Antarctica (Colesie et al, 2022). Amesbury et al (2017) have shown that with the Antarctic Peninsula becoming warmer and wetter, moss growth rates have quadrupled.…”
Section: Bryophytesmentioning
confidence: 99%